A review of effective doctoral supervision: what is it and how can we achieve it? - Masek, Alias; Alias, Maizam (Horizon Research Publishing, 2020)
The success of doctoral students greatly depends on effective supervision. Many factors however, are involved in ensuring effective supervision. This study identifies the different definitions of effective supervisions, types of doctoral outcomes and the associated factors that contribute to these outcomes, with a view of proposing a framework to achieve the goal of effective supervision. A systematic review was conducted on published articles from the year 2000 to the year 2018. The documents were selected based on the three major components of doctoral supervision namely, management system, students and supervisor, thus framing the systematic review. The review resulted in several key findings namely, definitions, domains of doctoral outcomes and factors that can potentially contribute to doctoral outcomes. Diverse definitions of effective supervision were observed; often associated with self-development, professional growth and career development of doctoral students. Four domains of doctoral outcomes were identified: knowledge-base, research skills, attitudes and professional skills. Factors that influence doctoral outcomes include environment, attitude and aptitude of doctoral students, and experience and training of supervisors. The findings of this review provide useful information for guiding the implementation of an effective supervision framework.